Processo avaliativo de tutores a distância em um curso de Pós-Graduação e reflexões sobre mudanças de condutas - Nunes, Vanessa Battestin (2012)
It was analyzed in this work the evaluation process of distance tutoring in a postgraduate course, with reflections about conduct changes occurred. This is a case study for the postgraduate course in Informatics in Education of CEAD/Ifes. An evaluation process was built in this context and can be adapted to other realities. Our focus was the distance tutor, an important actor in the students learning process. Bibliographic and documentary researchs and the participation of students and the course team contributed to generate four versions of the evaluation process. We analyzed the instruments created, which allowed the evaluation of distance tutors for different looks (students, teachers, presential tutors and self-assessment), as well as other monitoring methods: through virtual resources (especially by the Moodle learning environment) and face meetings (individual, discipline and team). The evaluation process aimed to help the distance tutors to better understand their role in the course and identify gaps in their work, seeking improvements and favoring thus awakenings and the constitution of a reflexive tutor. We analyze, in a quantitative and qualitative manner, the performance of distance tutors in the course disciplines, the impact of the evaluation process in their activities, the difficulties and problems encountered during their journey, conduct changes observed, resistances and advances. We used content analysis, triangulation and statistical method. Interviews were also conducted with a selected group of tutors. For construction of the evaluative process and to perform the analyzes we used, especially, the theories related to the constructivist and socio-historical conception of education. We achieved results that show that the evaluation process has contributed in improving the performance of distance tutors of the course, as: in the constitution of the tutor, in forming a reflective tutor, in the students monitoring, in supporting the knowledge construction of students, in communication with these and with team members, among others. Moreover, this work opens new perspectives for future study.